Coaching w perspektywie poradnictwa niedyrektywnego dla osób dorosłych - Jeruszka, Urszula (Kultura-Społeczeństwo-Edukacja, 2025)
The aim of the discussion is to show the possibilities and advantages of using coaching as a method in career quidance for adults. In a world of dynamic changes and increasing complexity, counselling understood as a one-time decision to indicate an individual’s profession, educational path or place in the labor market is being replaced by non-directive counseling addressed to every person, at every stage of their professional life. In non- directive counseling , coaching is a key method of work. It has been show that coaching excludes any directiveness on the part of the career counselor. The features principles and process approach to coaching in the context of counselling for adults are described. The sources of non- directive counseling resulting from the subjective theory of the concept of the individual by Rogers, the theory of learning from coincidences by Krumboltz and the theory of career construction by Savickas were analyzed. In the final part, two models of the coaching conversation as a counseling conversation are presented: the GROW model and the GOLD model.